(untitled) (Annals of Medical Research, 2021)
Aim: Endometrial cancer (EC) is mostly seen in elderly population, the impact of comorbid conditions on clinical outcomes and survival of EC is a topic of increasing interest. The aim of this study was to determine the association of diabetes mellitus (DM), hypertension (HT) and metformin use with survival in patients with EC.Material and Methods: Clinical and tumor characteristics of 410 patients who underwent surgery for EC in our institution between 2006 and 2012 were reviewed. Demographic features, histological subtypes, stage, type of surgery, comorbidities, treatment modalities and patient outcomes in terms of relapse-free survival (RFS) and overall survival (OS) were assessed.Results: Median follow-up was 39 months. The presence of HT and DM were associated with overall survival after adjusted for age, disease stage and grade (HR for HT 2.88, p=0.055, HR for DM 2.01, p=0.045). Presence of either HT or DM (or both) was independently associated with lower rate of 5 years survival (HR 8.24, p=0.041). Metformin use was not associated with RFS or OS in whole patient population. However, among patients with diabetes, metformin use was associated with improved 5 years survival (p=0.024) but not with RFS (p=0.47).Conclusion: Our study showed DM and HT to be associated with increased mortality in patients with EC but no link was shown between presence of DM/HT and disease recurrence. Metformin might be the treatment of choice in patients with DM and EC, but beneficial effects are probably through metabolic effects rather than anticancer efficacy.